Traditional Baduanjin exercise through the eyes of patients with chronic heart failure: A qualitative content analysis study - Chen, Xiankun; Jiang, Wei; Salazar, Mariano; Zhu, Huiying; Wen, Zehuai; Chen, Xixi; Lundborg, Cecilia Stålsby (Frontiers in Cardiovascular Medicine, 2023)
Objective Baduanjin (eight silken movements) is a traditional Chinese exercise that can be used as cardiac rehabilitation therapy for patients with chronic heart failure (CHF) especially when other forms of rehabilitation are scarce or unaffordable. This study explores the experiences of Chinese patients with CHF who undertook Baduanjin exercise at home as part of a pilot trial in Guangzhou, China. Methods We conducted seven qualitative interviews with participants who had participated in the intervention arm of a pilot randomized controlled trial (RCT) (n = 8). For data collection, we used a semi-structured interview guide with both open-ended, and follow-up questions. We audio recorded the interviews, transcribed them verbatim, and then analyzed them with content analysis. Results Participants’ experiences of doing Baduanjin were classified into three categories: (1) improving practice (2) factors facilitating good exercise adherence, and (3) feeling good. Participants reported that the exercises were easy but that the correct Baduanjin execution and coordination between the mind, movements, and breathing were only achievable through practice. In addition, the training benefits which they perceived were the predominant motivation for patients to keep practicing. Finally, trust in Baduanjin, personal attitudes toward health, flexibility in practice times, as well as social support helped the participants to achieve good adherence to home-based training. Conclusion This study’s findings indicate that Baduanjin could be a cardiac rehabilitation exercise modality for patients with CHF in China, especially in a home-based setting.